Mangroves of the Mekong: annual mapping of the status and changes of the world's mangroves. [Abstract only]. - Rebelo, Lisa-Maria (2013)
Mangroves are one of the most productive ecosystems globally, providing a wide range of ecosystem services and providing critical support to livelihoods. Although often associated with highly productive natural fisheries, mangrove forests are threatened in Southeast Asia in particular due to conversion to aquaculture. Despite their importance for livelihoods, carbon cycling and ecology, large uncertainties exist regarding the status and extent of mangroves globally. In addition changes in mangroves occur fast and updated information about their change status is required; for countries participating in REDD+, UNFCCC requires reporting at least on a bi-annual basis. Existing assessments of mangrove dynamics have typically focused on a limited number of discrete locations at fine detail using a variety of data types, and have not been documented and presented holistically. Until recently, routine detection of change in mangroves was problematic in many tropical and sub-tropical regions because of the persistence of cloud. Radar satellites can acquire data regardless of clouds, smoke and haze. The Global Mangrove Watch is an international collaborative project which aims to produce updated information about the worlds mangrove areas on an annual basis, and is being undertaken within the framework of the ALOS Kyoto and Carbon (K&C) initiative. This initiative revolves around the use of data gathered from JAXA's Phased Array L-band Synthetic Aperture Radar (PALSAR) on-board the Advanced Land Observation Satellite (ALOS) platform to support the information needs raised by international environmental conventions, carbon cycle science and the conservation of the environment. The K&C initiative builds upon the experience gained from the JERS-1 Global Rain Forest and Boreal Forest Mapping (GRFM/GBFM) projects which demonstrated the ability of L-band SAR for mapping and monitoring wetland areas at a spatial and temporal consistency. Under the Wetlands Theme of the K&C initiative, a set of key products are being generated, mapped and made publicly available, including the development of inventories of mangroves and associated peat swamp forests. An updated mangrove baseline and subsequent annual change maps is being produced using spaceborne radar images, primarily gathered from PALSAR. The dataset will be supported with additional radar imagery from the Japanese Earth Resource Satellite (JERS-1) where available. The Global Mangrove Watch is the first assessment of mangrove dynamics across the tropics, with results that are directly comparable between regions due to the consistency of the time period over which the imagery was gathered. This dataset will enable a comprehensive assessment of the status of and changes in mangrove ecosystems globally.